Analysis of a Diimine‐Organonickel Redox Series - Sondermann, Christina; Pižl, Martin; Paretzki, Alexa; Feil, Christoph; Ringenberg, Mark R.; Záliš, Stanislav; Kaim, Wolfgang (European journal of inorganic chemistry, 2020)
Complex cations [Ni(C5R5)(L)]+, L = 1,4‐diphenyl‐2,3‐dimethyl‐1,4‐diaza‐1,3‐butadiene, were compared as structurally characterized BF4– (R = H) and SbF6– salts (R = Me). These NiII(L0) compounds are reversibly reduced (R = H,Me) or oxidized (R = Me) and their one‐electron oxidized and reduced forms studied by EPR and UV/Vis spectroelectrochemistry, supported by DFT calculations. Surprisingly similar EPR features were observed for [Ni(C5Me5)(L)]0 and [Ni(C5Me5)(L)]2+. Whereas the oxidation is largely metal centered to yield a NiIII species (R = Me), the reduction reveals energetically close‐lying alternatives (redox isomers) NiI(L0) and NiII(L·–). A rare case of innocent α‐diimine ligand behavior and mostly metal‐based electron transfer has been evidenced for [Ni(C5Me5)(L)]n, n = 0,+,2+, and L = 1,4‐diphenyl‐2,3‐dimethyl‐1,4‐diaza‐1,3‐butadiene via spectroelectrochemistry and DFT.